The Profile Characteristics of Muga Silkworm Rearers of the Sonitpur District of Assam, India - Dababrata Saikia; Dipankar Saikia; Monimala Saikia; Debajit Borah (Archives of Current Research International, 2024)
A study was conducted during 2020-2021 to analyze the profile characteristics of 120 muga rearers of the Sonitpur district of Assam. The study revealed that the majority of the respondents (42.50%) belonged to the middle age group. Most of the respondents (47.50%) belonged to the category OBC (Other Backward Class) and had their (35.00%) education up to middle school. Among the respondents, medium-sized (50.00%) family was found to be dominant and farming was their primary occupation with a medium level of income ranging from Rs. 52,000-1,71,000. Regarding the size of operational land holding, the majority (40.83%) of the muga farmers owned operational land holding of 1-2 ha. The majority of the respondents (48.33%) had farming experience between 10-20 years. It was also observed that most of the respondents had a medium level of extension contact (73.33%), medium risk-bearing ability (65.83%), medium decision-making ability (60.83%), and a medium level of marketing orientation (69.17%). As regards training exposure, only 27.50 percent of the respondents had received any training.